2017
DOI: 10.1038/mi.2016.95
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of a recombinant cholera toxin B subunit promotes mucosal healing in the colon

Abstract: Cholera toxin B subunit (CTB) is a component of a licensed oral cholera vaccine. However, CTB has pleiotropic immunomodulatory effects whose impacts on the gut are not fully understood. Here, we found that oral administration in mice of a plant-made recombinant CTB (CTBp) significantly increased several immune cell populations in the colon lamina propria. Global gene expression analysis revealed that CTBp had more pronounced impacts on the colon than the small intestine, with significant activation of TGFβ-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(97 citation statements)
references
References 49 publications
11
85
0
1
Order By: Relevance
“…Given that chronic inflammation and injury of the bowel, such as inflammatory bowel disease (IBD), pose an increased risk of developing colitis-associated colorectal cancer (CAC) [24,25,100,101], CTB-KDEL's effects were also examined in the azoxymethane (AOM)/DSS mouse model of CAC. Biweekly oral administration of CTB-KDEL over 9 weeks significantly reduced inflammation and tumorigenesis in this model, highlighting its therapeutic potential in intestinal injury and inflammatory bowel disease, such as ulcerative colitis (UC) [50]. Therefore, the finding that CTB-KDEL is a topical agent that facilitates TGFβ-based mucosal wound healing in UC and CAC mouse, supports a hypothesis that CTB-KDEL could help address important issues pertinent to therapeutic strategies for mucosal healing in UC.…”
Section: A Plant-made Ctb Variant (Ctb-kdel) Directly Modulates Epithmentioning
confidence: 54%
See 4 more Smart Citations
“…Given that chronic inflammation and injury of the bowel, such as inflammatory bowel disease (IBD), pose an increased risk of developing colitis-associated colorectal cancer (CAC) [24,25,100,101], CTB-KDEL's effects were also examined in the azoxymethane (AOM)/DSS mouse model of CAC. Biweekly oral administration of CTB-KDEL over 9 weeks significantly reduced inflammation and tumorigenesis in this model, highlighting its therapeutic potential in intestinal injury and inflammatory bowel disease, such as ulcerative colitis (UC) [50]. Therefore, the finding that CTB-KDEL is a topical agent that facilitates TGFβ-based mucosal wound healing in UC and CAC mouse, supports a hypothesis that CTB-KDEL could help address important issues pertinent to therapeutic strategies for mucosal healing in UC.…”
Section: A Plant-made Ctb Variant (Ctb-kdel) Directly Modulates Epithmentioning
confidence: 54%
“…Besides the specific T helper cell subsets, our study has also revealed that innate immune cells-including dendritic cells, natural killer cells and macrophages (both M1 and M2)-populations were increased in the colon lamina propria two weeks after CTB-KDEL oral administration [50]. Furthermore, a global gene expression analysis revealed that CTB-KDEL had more pronounced impacts on the colon than the small intestine, with significant activation of TGFβ-mediated pathways in the colon mucosa [50]. Given that there is a strong link between epithelial-derived TGFβ and innate immune cells in wound healing [92][93][94], the results provided implications for the potential utility of CTB-KDEL to promote colonic mucosal health.…”
Section: A Plant-made Ctb Variant (Ctb-kdel) Directly Modulates Epithmentioning
confidence: 64%
See 3 more Smart Citations